Soil-hydro-physical studies. II Utinga soil - Oliveira, Luiz Bezerra de; Melo, Valdemir de (Pesquisa Agropecuaria Brasileira, 2014)
Seventeen soil profiles of Utinga soil (Red-yellow distrophic latosol) were analytically studied. This soil occurs in the Northeastern Brazil in humid region of the states of Pernambuco and Alagoas. The soil samples (undisturbed soil samples) were collected by means of a soil extractor apparatus and by usual methods. The purpose of the study was to establish hydric and physical data to be used in irrigation practices and soil management. It was concluded that Utinga soil is deep and porous without compaction problems, with medium texture at the surface and clay in the B horizon. It has medium available water capacity, medium to high permeability at the surface, and medium in the lower layers. The soil has a low base exchange capacity, high acidity, and low fertility. The soil was classified as Class II for use capacity, in Class III for its agriculture capabilities in primitive management, and in Class I for its advanced management. A higher productivity may be obtained with a rational use of limestone, fertilizers, and suplementary irrigation.